Experimental study of the aragonite to calcite transition in aqueous solution - Perdikouri, C.; Kasioptas, A.; Geisler, T.; Schmidt, B.; Putnis, Andrew (2011)
The experimental replacement of aragonite by calcite was studied under hydrothermal conditions at temperatures between 160 and 200 °C using single inorganic aragonite crystals as a starting material. The initial saturation state and the total [Ca2+]:[CO32−] ratio of the experimental solutions was found to have a determining effect on the amount and abundance of calcite overgrowths as well as the extent of replacement observed within the crystals. The replacement process was accompanied by progressive formation of cracks and pores within the calcite, which led to extended fracturing of the initial aragonite. The overall shape and morphology of the parent aragonite crystal were preserved. The replaced regions were identified with scanning electron microscopy and Raman spectroscopy.Experiments using carbonate solutions prepared with water enriched in 18O (97%) were also performed in order to trace the course of this replacement process. The incorporation of the heavier oxygen isotope in the carbonate molecule within the calcite replacements was monitored with Raman spectroscopy. The heterogeneous distribution of 18O in the reaction products required a separate study of the kinetics of isotopic equilibration within the fluid to obtain a better understanding of the 18O distribution in the calcite replacement. An activation energy of 109 kJ/mol was calculated for the exchange of oxygen isotopes between [C16O32−]aq and [H218O] and the time for oxygen isotope exchange in the fluid at 200 °C was estimated at ∼0.9 s. Given the exchange rate, analyses of the run products imply that the oxygen isotope composition in the calcite product is partly inherited from the oxygen isotope composition of the aragonite parent during the replacement process and is dependent on access of the fluid to the reaction interface rather than equilibration time. The aragonite to calcite fluid-mediated transformation is described by a coupled dissolution–reprecipitation mechanism, where aragonite dissolution is coupled to the precipitation of calcite at an inwardly moving reaction interface.